Equity valuation of Advanced Micro Devices (AMD) - Sousa, João Vaz de (2021)
The main objective of this thesis is to develop a valuation of Advanced Micro Devices (AMD) based on fundamental analysis and development of financial models using methods such as the discounted cash flows and relative valuation. Firstly, an in-depth analysis of the company is presented to get a better view of its overall position, focusing on its segments, strategy, and financial performance. Secondly, an analysis of the industry of semiconductors is made to get a scope of the macroeconomic environment in which AMD is inserted. Lastly, financial models are presented using methods based on the review of literature and used to draw conclusions on AMD’s final valuation. Another topic tied to this valuation is Mergers & Acquisitions (M&A), with the acquisition of Xilinx by AMD being a very high focus point to study the recent high growth of AMD and the acquisition of Arm by Nvidia to study the future of the semiconductors industry. The final results of the valuation showed a fair share price for AMD of $114.54 and $105 using a perpetuity and exit EBITDA multiple approaches, respectively. For the scenario of conclusion of Xilinx acquisition by AMD, the fair share price presented was $123.29 for the perpetuity approach and $119.56 for the exit EBITDA multiple approach. These results were compared to the current market price of $105.8 (as of September 24th, 2021) and used as a foundation to issue a final recommendation of “Buy” on AMD’s stock.